An Octanuclear Metallosupramolecular Cage Designed To Exhibit Spin‐Crossover Behavior. Issue 18 (30th March 2017) - Struch, Niklas; Bannwarth, Christoph; Ronson, Tanya K.; Lorenz, Yvonne; Mienert, Bernd; Wagner, Norbert; Engeser, Marianne; Bill, Eckhard; Puttreddy, Rakesh; Rissanen, Kari; Beck, Johannes; Grimme, Stefan; et al.
Abstract: By employing the subcomponent self‐assembly approach utilizing 5, 10, 15, 20‐tetrakis(4‐aminophenyl)porphyrin or its zinc(II) complex, 1 H ‐4‐imidazolecarbaldehyde, and either zinc(II) or iron(II) salts, we were able to prepare O‐symmetric cages having a confined volume of ca. 1300 Å 3 . The use of iron(II) salts yielded coordination cages in the high‐spin state at room temperature, manifesting spin‐crossover in solution at low temperatures, whereas corresponding zinc(II) salts led to the corresponding diamagnetic analogues. The new cages were characterized by synchrotron X‐ray crystallography, high‐resolution mass spectrometry, and NMR, Mössbauer, IR, and UV/Vis spectroscopy. The cage structures and UV/Vis spectra were independently confirmed by state‐of‐the‐art DFT calculations. A remarkably high‐spin‐stabilizing effect through encapsulation of C70 was observed. The spin‐transition temperature T 1/2 is lowered by 20 K in the host–guest complex. Abstract : Subcomponent self‐assembly results in octanuclear metallosupramolecular cages, which were structurally characterized by experimental and theoretical means. The iron(II) cages undergo spin‐crossover in solution. This behavior is guest‐dependent, as encapsulation of fullerene C70 stabilizes the high‐spin state and shifts the spin‐transition temperature by as much as 20 K.